Integrating the active OER and HER components as the heterostructures for the efficient overall water splitting - Wu, Aiping; Xie, Ying; Ma, Hui; Tian, Chungui; Gu, Ying; Yan, Haijing; Zhang, Xiaomeng; Yang, Guoyu; Fu, Honggang (Nano energy, 2018)
Developing the efficient and low-cost electrocatalysts for overall water splitting is of the great importance for the production of H2. The popular bi-functional catalysts usually shown good activity for one half reaction at expense of the activity for another half-reaction, thus given a moderate performance for overall water splitting. In this paper, we have reported on integrating the active OER (Ni3N) and HER (NiMoN) components as Ni3N-NiMoN heterostructures for the effective overall water splitting. The heterostructures were constructed by the controllable nitridation of the Ni-Mo-O precursor anchored on carbon cloth (CC) under NH3 atmosphere. The micro-structures of the catalyst could be tuned by regulating the surface properties of CC and the calcination temperature. Under optimized condition, the Ni3N-NiMoN catalysts exhibited good catalytic activity for both OER and HER in alkaline electrolyte. The catalysts can achieve a current density of 10mAcm−2 at an overpotential of 31mV for HER, being close to Pt catalyst. Also, it only requiring an overpotential of 277mV to reach current density of 10mAcm−2 for OER. Moreover, the cell assembled by the identical Ni3N-NiMoN as both the cathode and anode needs only a cell voltage of 1.54V to achieve current density of 10mAcm−2. The superior performance of Ni3N-NiMoN heterostructures can be ascribed to the following points: 1) the simultaneous presence of active OER and HER components and the promoted action each other in the heterostructures, and 2) the exposure of the abundant active sites in the sheet-like structure assembled by the nanoparticles. The OER-active Ni3N and HER-active NiMoN have been integrated as Ni3N-NiMoN heterostructures anchored on carbon cloth for the high-effective overall water splitting. The catalysts can achieve a current density of 10mAcm−2 at an overpotential of 31mV for HER and an overpotential of 277mV for OER. The cell assembled by Ni3N-NiMoN heterostructures as both the cathode and anode only needs a cell voltage of 1.54V to achieve 10mAcm−2 for overall water splitting. [Display omitted] •The active OER and HER components are integrated as Ni3N-NiMoN heterostructures.•The heterostructures show good performance for both HER and OER.•The heterostructures exhibit superior performance for overall water splitting.•The origin of superior performance of the heterostructures is elucidated.